2023
DOI: 10.3390/w15040686
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence Characterization and Contamination Risk Evaluation of Microplastics in Hefei’s Urban Wastewater Treatment Plant

Abstract: As one of the primary nodes in the flow of micro-plastics (MPs) in the environment, it is critical to examine and assess the Sewage Treatment, occurrence, and removal of MPs in waste treatment plant (WWTP). This research explored the shape, size, and composition of MPs at various stages of the WWTP process in the south of the city of Hefei, China, in dry and rainy weather conditions, as well as the removal effectiveness of MPs in a three-stage process. The collected MPs were quantitatively and qualitatively ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…According to Table 1, the average value of MPs abundance in domestic effluent is 46.94 n/L, and according to the daily effluent treatment volume of 144 million m 3 in China's WWTPs in 2019, it can be estimated that China's WWTPs will discharge 6.76×10 12 MPs into the natural environment every day. Most of the MPs removed in sewage plants are retained in the sludge, and the average value of MPs abundance in sewage treatment plant sludge shown in the statistics of Table 2 is 3.80×10 4 n/Kg, which, combined with the national production of sludge, roughly estimates that MPs entering the environment through the sludge in our country every year will be as high as 1.89×10 14 MPs.…”
Section: Characterisation Of Mps Assignment In Wwtpsmentioning
confidence: 95%
“…According to Table 1, the average value of MPs abundance in domestic effluent is 46.94 n/L, and according to the daily effluent treatment volume of 144 million m 3 in China's WWTPs in 2019, it can be estimated that China's WWTPs will discharge 6.76×10 12 MPs into the natural environment every day. Most of the MPs removed in sewage plants are retained in the sludge, and the average value of MPs abundance in sewage treatment plant sludge shown in the statistics of Table 2 is 3.80×10 4 n/Kg, which, combined with the national production of sludge, roughly estimates that MPs entering the environment through the sludge in our country every year will be as high as 1.89×10 14 MPs.…”
Section: Characterisation Of Mps Assignment In Wwtpsmentioning
confidence: 95%
“…To identify the level of error and contamination during sample preparation and testing, 4 distilled water samples were kept in the testing environment for 7 days. In addition, nitrate cellulose (NC) lters (4 lters on the Petri dish) were placed near the microscope, hood, and the testing environment for 7 days (Jiang et al, 2020;Meng et al, 2023;Shari et al, 2023).…”
Section: Quality Control and Quality Assurancementioning
confidence: 99%
“…Fionn Murphy et al conducted a study on microplastics in the e uent of a wastewater treatment plant in 2016, which revealed the following microplastic counts: 51.7 N/l at the in uent and 0.25 N/l at the e uent of the treatment plant. In this treatment plant, the e ciency of microplastic removal has been 98 41…”
mentioning
confidence: 99%
“…To identify the level of error and contamination during sample preparation and testing, 4 distilled water samples were kept in the testing environment for 7 days. In addition, nitrate cellulose (NC) lters (4 lters on the Petri dish) were placed near the microscope, hood, and the testing environment for 7 days (Jiang et al, 2020;Meng et al, 2023;Shari et al, 2023).…”
Section: Quality Control and Quality Assurancementioning
confidence: 99%